Potensi Fermentasi Bawang Putih Tunggal Hitam (Allium sativum L.) Sebagai Alternatif Antikolesterol - Desi Sri Rejeki; Ery Nourika Alfiraza; Tika Amelia (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Cholesterol is a fatty substance that circulates in the blood and is yellowish in color, and has a texture similar to wax, produced by the liver and is needed by the body. One plant that can lower cholesterol is single black garlic. This study aims to determine the anti-cholesterol content at various fermentation times for single black garlic. The research was carried out using single black garlic samples with fermentation times of 5, 10 and 15 days. One alternative that can be chosen to lower cholesterol levels is to consume single garlic into single black garlic, fermentation produces a sweeter and softer taste and reduces the sharp taste and aroma of fresh garlic, making it more preferred by many people. Samples were analyzed quantitatively using UV-Vis spectrophotometry. The maximum λ value was obtained at 636.5 nm with the linear regression equation y = 0.0002x + 0.3098 and (r) at 0.9945. In quantitative tests, all variations in fermentation time can reduce cholesterol. Fermentation samples for 5, 10 and 15 days respectively obtained an EC50 value of 1067.07; 1185.5; 1354.65 ppm, while the positive control simvastatin got an EC50 value of 961.25 ppm. It can be concluded that the best fermentation time is 5 days of fermentation because the smaller the EC50 value, the stronger the anti-cholesterol power.